TGFβ level in healthy and children with Marfan syndrome—effective reduction under sartan therapy - Stark, Veronika C.; Olfe, Jakob; Diaz-Gil, Daniel; von Kodolitsch, Yskert; Kozlik-Feldmann, Rainer; Reincke, Johannes; Stark, Maria; Wiegand, Peter; Zeller, Tanja; Mir, Thomas S. (Frontiers in Pediatrics, 2024)
Introduction Transforming growth factor β (TGFβ) metabolism plays an important role in the pathogenesis of Marfan syndrome (MFS). Accordingly, drug therapy uses TGFβ receptor blockade to slow down the cardiovascular manifestations, above all aortic root dilatation. Angiotensin II type 1 receptor blockers (ARBs) have been shown to reduce TGFβ levels in adults. Data on childhood are lacking and are now being investigated in the TiGer For Kids study presented here. Methods We examined 125 children without chronic disease and 31 pediatric Marfan patients with a proven FBN1 variant with regard to TGFβ levels. In addition, we measured TGFβ levels during the initiation of ARB therapy in pediatric Marfan patients. Results In children without chronic disease, TGFβ levels were found to decrease from childhood to adolescence (p < 0.0125). We could not measure a relevantly increased TGFβ level in pediatric Marfan patients. However, we showed a significant suppression of the TGFβ level after treatment with ARBs (p < 0.0125) and a renewed increase shortly before the next dose. Discussion The TGFβ level in childhood changes in an age-dependent manner and decreases with age. The TGFβ level drops significantly after taking ARBs. Based on our experience and data, a TGFβ receptor blockade in childhood seems reasonable. So far, TGFβ level cannot be used as an MFS screening biomarker.